Análise do alinhamento estratégico no portfólio de P&D - Veronica Mariana Oliveira Soares (2014)
The firms primary goal is establish a sustained competitive advantage and strategy is a key to reach it. However, decision-makers have some difficulties translating strategy to portfolio. The Strategic Buckets Method is an alternative to deal with them. Thus, the main question of this work is how to establish the set of buckets aligning the R&D portfolio to business strategy. To tackle this question, we developed, at first, a theoretical framework based on a major literature review. The framework is composed of four strategic constructs (Technology, Marketing, Capabilities and Organizational Processes), and the External Environment, each one with a set of key factors. Then, we proceeded with seven case studies of market leaders companies (e.g., Natura, Vale, Petrobras, Nova Pontocom, Itaú, Fiat and Embraer). By contrasting the theoretical framework and the cases studies, we found some evidences that the constructs are relevant in portfolio decisions. We ground some theoretical insights about the configuration of strategic constructs, which can be combined and split, resulting in a set of buckets to suit the companys strategy.